Echographie Doppler Arterielle Testiculaire Dans L’infertilite Masculine A Lome - A., Amadou; L., Sonhaye; B., Douaguibe; M., Tchaou; KA., Agbangba; G., Watara; V., Adjenou; K., N’dakena (European Scientific Journal, ESJ, 2017)
Objective: Determine the relationship between the testicular arterial resistance index (IR) and spermatogenesis. Material and method: prospective analytical study over a period of 12 months at CHU campus and National Institute of Hygiene of Lomé. The parameters studied were anomalies of sperm count, sperm volume, testis volume, and resistance index (RI). The study of the correlation between our variables was done using the Chi square test (χ2). Results: The mean age of men was 36.26 years. Sperm volume was normal in 73% men and abnormal in 27% men. 65% had normal sperm counts, and 35% had abnormal sperm counts. The normal testicular volume was found in 42% men and 58% had an abnormal testicular volume (hypotrophic testis). 51% men had the pathological RI while 49% had a normal RI. There was no statistically significant relationship between testicular volume and sperm count. Also, no statistically significant relationship between RI and testicular volume. But, there was a statistically significant correlation between RI and sperm count. No statistically significant difference between RI and sperm volume. Conclusion: RI can be used with sperm analysis and hormonal studies as part of the clinical evaluation of infertile men. An intratesticular RI greater than 0.6 is associated with decreased total motile sperm.